Proposal of a new PPG-based watch-like device for Heart rate and BP measurement with GPS facility - Banerjee, Anindita; Bandyopadhyay, Dipan; Tunga, Santasri Giri (International Journal of Computer Sciences and Engineering, 2025)
PPG signal may be considered as an important diagnostic platform for measurement of different physiological indices for cardiovascular disease. PPG detects volumetric changes in arterial vessels that cause a change in the light absorption, reflection and therefore the light intensity detected by the photo detector. Our proposed research topic primarily deals with performing data acquisition of raw PPG signal from a Spo2 sensor based blood pressure measuring system. The PPG signal thus acquired will be processed for different noise removal using suitable filtering and smoothening methods. Thereafter analysis of the PPG signal could be done with the help of signal processing method for feature extraction like Spo2 value, Pulse rate, Heart Rate Variability, Blood flow rate, Arterial stiffness, Augmentation index etc. all of which contribute to arterial pressure can be calculated from the PPG waveform itself. All these physiological parameters extracted from PPG signal would result in an overall analysis of patient’s cardiovascular condition. Each of the parameter calculated from the real time PPG signal would be then clinically standardized and finalized for remote transmission wirelessly resulting in immediate diagnosis in case of emergency. The measured HR and BP can be displayed on a LCD watch or ring-like proposed instrument and using GPS, MCU and ITTT website, an auto message can be sent to his/her family member during any emergency stating the condition BP, HR and location of the person.